(untitled) (International journal of artificial intelligence, 2024)
Over the past 6 years, within the framework of the implementation of measures for the fundamental reform and improvement of the healthcare sector of the Republic of Uzbekistan, special attention is paid to significantly improving the quality of state-guaranteed services for the provision of emergency medical care to the population, primarily to increasing the efficiency and effectiveness of the ambulance service. In particular, as a result of the implementation of measures defined by the Decree of the President of the Republic of Uzbekistan dated March 16, 2017 No. UP-4985 "On measures to further improve the emergency medical care system", Resolutions of the President of the Republic of Uzbekistan dated March 16, 2017 No. PP-2838 "On measures to further strengthen the material and technical base and organization of the emergency medical care system", dated January 25, 2018 No. PP-3494 "On measures to accelerate the improvement of the emergency medical care system" , dated October 16, 2018 No. PP-3973 "On measures to improve the ambulance service in the Republic of Uzbekistan" and dated June 16, 20 22 No. PP-283 "On improving the system of providing emergency medical care to the population" The Republican Center for Emergency Medical Care and 14 of its regional branches were created on the basis of the emergency medical care service and medical vehicle fleets, and a unified vertical management system of emergency medical care , the organizational foundations of the functioning of the emergency medical care service have been optimized, its funding has been increased many times over, centralization of drug provision and targeted allocation of funds for service units have been ensured.